The genesis of the obligation to protest the motherland during the revival of the Ukrainian state (1917-1921) - Ukhach, Vasyl (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The article is devoted to clarifying the peculiarities of the legal (constitutional) consolidation of the obligation to protect the Motherland at the stage of the revival of the Ukrainian state during the period of 1917-1921.The purpose of the article is to analyze the historical prerequisites for the occurrence of military service and its legal (constitutional) regulation on the territory of Ukraine in the context of the protection of the Motherland.It is claimed that the process of forming (reforming) the effective legal framework of the Armed Forces of Ukraine is necessarily connected with the study and consideration of the historical experience of the evolution oflegislation throughout the centuries-old history of the Ukrainian state formation.It is proven that the formation of states contributed to the formation of the beginnings of the organization of military structures, which not only defense functions relied on, but also solving of internal political issues. Growingattention to the issues of military duty, building and provision of the army, led to the need for legal regulation of the system of military legislation. Military construction during the period of the national liberation struggle of 1917-1921 was one of the priority policy issues of Ukrainian governments, but was not always properly implemented in practice.The armed aggression of the russian federation against Ukraine, which began on February 24, 2022, necessitated the fundamental reform of the legislation in the field of defence and national security, taking into account the declaredEuropean integration and Euro-Atlantic perspectives.